Tubercular granuloma arising from floor of orbit : A rare occurrence - Khan, Lubna (Nepalese Journal of Ophthalmology, 2022)
Introduction: Tuberculosis of the orbit is a unilateral entity commonly involving the bony wall, periosteum or soft tissue in left orbit. It is a rarity. Case: A fifty seven years old female presented with a localised mass near inferior orbital margin. Owing to its small size and superficial location in orbit, there was no soft tissue displacement or motility disturbance. Observations: Dissection revealed a localised firm mass attached to periorbita covering the orbital floor. The mass was excised and on histopathological analysis it was found to be composed of multiple granulomas containing abundant Giant cells. Considering such a picture at cellular level, ELISA for tuberculosis was done. Values were suggestive of recent infection. The patient was put on antitubercular multidrug regimen for six months one week after excision of mass, with a follow up of four years, having no recurrence till date. Conclusion: Though orbital tuberculosis is much more common in childhood, it should always be considered in the differential diagnosis of orbital mass in adults also. At times, even in an otherwise healthy individual, tuberculosis might be diagnosed because of an orbital mass. Ophthalmologists should have a high index of suspicion since orbital tuberculosis has been underdiagnosed in the past.